When it is available, will you pay for it? A Systematic Review and Meta-analysis of Willingness to Pay (WTP) for Malaria Vaccines in Africa - Effiong Fortune Benjamin; Hassan Ibrahim Adebayo; Ekpor Emmanuel; Olawuyi Dimeji Abdulsobur; Araoye Jeremiah Babatunde; Dine Roseline Dzekem; Asori Moses (My University, 2024)
Background: Malaria vaccination holds significant potentials for combating malaria in Africa and its implementation is underway in many endemic countries. However, the economic climate on the continent raises concerns around sustainable financing for the program. Yet, evidence of the willingness to pay (WTP) for the vaccines by Africans in a cost-based provision model is unclear. Therefore, this systematic review and meta-analysis aims to summarize the available evidence of the WTP for the malaria vaccines in Africa. Methods: We conducted a systematic search for relevant literatures in databases such as PubMed, Scopus, Google Scholar, and CENTRAL following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines and our inclusion criteria. The primary outcome measures included the WTP proportion, prices, and determinants for any malaria vaccine reported in any African country since the year 2000. We applied the DerSimonian-Laird random-effects meta-analysis for effect estimation, with the pooled results presented alongside 95% confidence intervals (CI) calculated using the Clopper-Pearson method. Results: Of the 1,398 literature screened, 8 studies reporting WTP data for 6102 adults and primary caregivers from 6 African countries were included in the final analysis. The pooled proportion of the WTP was 85.9% (95% CI: 76.0–92.1), with significant heterogeneity (I2 = 98%, p < 0.01). However, the average prices participants were willing to pay varied across countries. The WTP prices ranged from approximately $1 in Sierra Leone to $8.03 in Nigeria for adults, and from $0.69 in Sierra Leone to $26.90 in Ethiopia for children. The review identified a host of sociodemographic, vaccine-related, and situational factors influencing African adults and caregivers WTP for the malaria vaccines. Participants' levels of income (ability to pay) and education were frequently reported determinants of WTP. Conclusion: There is a shortage of studies on the WTP for malaria vaccines in Africa. We found a seemingly high WTP level for the malaria vaccines in Africa, delimited by income and educational levels across households and countries. African health policymakers should consider their local realities to deliver an equitable yet sustainable malaria vaccination program. Keywords: vaccines; willingness to pay (WTP); malaria; meta-analysis
We would like to acknowledge the African Community for Systematic Reviews and Meta-Analyses (ACSRM) for facilitating this review through their platform and network. We also thank facilitators from AuthorAID/INASP for their contributions to our understanding of systematic review methodologies.